Social Finance And Unconventional Financing Alternatives: An Overview - Biancone, Paolo Pietro; Radwan, Maha (European Journal of Islamic Finance, 2018)
The economic crisis, the increment of poverty and unemployment, the emergence of several social problems, and the limitations of the public spending have all called for exploring innovative and alternative ways of social financing. Such enterprises face many challenges in accessing finance due to that high risk regarding generating profit, problems of governance model, and lacks of performance measurement valuations especially when it comes to measuring social value. There is a need for finance impact driven businesses and this requires the reinforcement of current funding alternatives and usage of innovative financing alternatives. Islamic finance with its unconventional wide range instruments represents a possible potentiality for offering innovative financing alternative. The paper is exploratory and should give insights to the emerging interest in both social impact finance and Islamic finance with its innovative tools that focus on risk sharing and social impact. This paper argues that unconventional financing alternatives could positively impact international economies and be a viable potential alternative for financing with its diversified instruments for social enterprises development. The paper explores the different unconventional instruments of financing as well as the criteria of accessing them. The paper provides insights for researchers, decision makers, and practitioners of how could be unconventional financing used as valid financing tool for social impact businesses.